From genes to treatments: a systematic review of the pharmacogenetics in smoking cessation. (19th June 2018) - Salloum, Naji C; Buchalter, Erica LF; Chanani, Swati; Espejo, Gemma; Ismail, Mahjabeen S; Laine, Randy O; Nageeb, Maysaa; Srivastava, A Benjamin; Trapp, Nicholas; Trillo, Ludwig; Vance, Erica; Wenzinger, Michael; et al.
Smoking cessation treatment outcomes may be heavily influenced by genetic variations among smokers. Therefore, identifying specific variants that affect response to different pharmacotherapies is of major interest to the field. In the current study, we systematically review all studies published in or after the year 1990 which examined one or more gene–drug interactions for smoking cessation treatment. Out of 644 citations, 46 articles met the inclusion criteria for the systematic review. We summarize evidence on several genetic polymorphisms ( CHRNA5-A3-B4, CYP2A6, DBH, CHRNA4, COMT, DRD2, DRD4 and CYP2B6 ) and their potential moderating pharamacotherarpy effects on patient cessation efficacy rates. These findings are promising and call for further research to demonstrate the effectiveness of genetic testing in personalizing treatment decision-making and improving outcome.